2018
DOI: 10.1111/joa.12870
|View full text |Cite
|
Sign up to set email alerts
|

A morphoanatomical approach to the adaptive features of the epidermis and proboscis of a marine Polychaeta: Eulalia viridis (Phyllodocida: Phyllodocidae)

Abstract: Eulalia viridis is a marine Polychaeta of the rocky intertidal that, despite its simple anatomy, is an active predator of much larger invertebrates, from which it extracts pieces of soft tissue through suction. This uncanny feeding strategy triggered the pursuit for the morphological mechanisms that enable adaptation to its environment. The evaluation of the worm anatomy and microanatomy, combining electron and optical microscopy, revealed a series of particular adaptations in the epidermis and in the probosci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 47 publications
(122 reference statements)
1
23
0
Order By: Relevance
“…It was previously noted that Eulalia does not possess complex chromatophores and owes its bright-green colour to specialised cells distributed along the skin that store the pigments in non-fluorescent cytoplasmic granules 20 . The distribution of pigment cells in the species is similar to what would be expected for melanins, for which no evidence was found asides nerve cord and eyes 21,22 . In line with the interest in porphyrins as potential photosensitisers and their physiological role as protective pigments, the aims of this study are: i) to evaluate the diversity and distribution of the pigments along E. viridis body, ii) to infer their basic spectroscopic properties and stability and iii) to contribute to understand the pigments’ adaptative value and their main functions.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…It was previously noted that Eulalia does not possess complex chromatophores and owes its bright-green colour to specialised cells distributed along the skin that store the pigments in non-fluorescent cytoplasmic granules 20 . The distribution of pigment cells in the species is similar to what would be expected for melanins, for which no evidence was found asides nerve cord and eyes 21,22 . In line with the interest in porphyrins as potential photosensitisers and their physiological role as protective pigments, the aims of this study are: i) to evaluate the diversity and distribution of the pigments along E. viridis body, ii) to infer their basic spectroscopic properties and stability and iii) to contribute to understand the pigments’ adaptative value and their main functions.…”
Section: Introductionsupporting
confidence: 63%
“…In either case, it is suggested that the pigments from E. viridis hold a dual function in protecting the animal from sunlight. Besides photoreception, green pigments can take part in other sensory function, as they are present in the mechanoreceptors in the papillae of the proboscis, and in the pigment cells of skin, the latter of which possess cilia that protrude through the cuticle, being hypothesised to have a sensory-like function 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering that Eulalia is a diurnal forager of the rocky intertidal, its pigments likely have two important roles. First, they are either toxic or repellent to predators and parasites that cause rupture to the pigment cells where the pigments are “safely” stored in granules [ 19 , 20 ]. Second, they warn of excessive exposure to daylight by causing physiological stress, which can be considered a form of non-nervous sensorial arrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Second, they warn of excessive exposure to daylight by causing physiological stress, which can be considered a form of non-nervous sensorial arrangement. The fact that Eulalia uses its proboscis as the main organ for sensing and preying [ 19 , 21 ] explains the natural difference between the pigmentation of the skin as a major adaptive trait. These particular features, which are probably not circumscribed to Eulalia or even to the Order Phyllodocida, show that the Polychaeta are very promising targets for the bioprospecting of photoactive tetrapyrrolic pigments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation